Serum IgA, IgG, IgM levels, total protein (TP), albumin (ALB) changes in elderly hip fracture patients after surgery and nutritional support - Jin Fangqin; Zhang Qin; Weng Jiangping; Pan Xuting; Dong Qinyan; Zhao Yuping (Journal of Medical Biochemistry)
Background: This study aimed to evaluate the effects of nutritional support combined with stratified nursing under delirium risk assessment on immune function and postoperative delirium in elderly hip fracture patients. Methods: A total of 112 elderly hip fracture patients were divided into two groups: the study group (SG), which received stratified nursing and enteral nutrition, and the control group (CG), which received routine nursing with a normal diet. Key parameters were evaluated and compared, including serum IgA, IgG, IgM levels, total protein (TP), albumin (ALB), postoperative delirium incidence, nutritional status, recovery time, and overall patient outcomes. Results: Compared to the CG, the SG demonstrated significant improvements in immune function, with increased IgA, IgG, and IgM levels, as well as higher haemoglobin, albumin, and total protein levels. The SG also experienced shorter hospital stays, earlier postoperative mobility, reduced postoperative delirium rates (1.79% vs. 14.29%), lower anxiety and depression scores, better sleep quality, and lower pain scores. Additionally, nursing satisfaction was significantly higher in the SG. Conclusions: Nutritional support combined with stratified nursing under delirium risk assessment effectively enhances immune function, reduces postoperative delirium, and accelerates recovery in elderly hip fracture patients. This approach may serve as a valuable strategy in postoperative management to improve patient outcomes.